Oscar Schlemmer's Triadic Ballet (Paris, 1932) and Dance Discourse in Germany. Three Letters with Annotation and a Commentary - Kant, Marion 1951- (Edinburgh: Edinburgh University Press, 2015)
RESUMEN: Three letters, exchanged in 1932 between the critic Artur Michel and the painter and choreographer Oskar Schlemmer, illuminate the complicated relationship between modern dance advocates in general and attitudes to the Triadic Ballet in particular in the last years of the Weimar Republic. They inform us of the way in which the representatives of different dance aesthetics dealt with their opposing views.